Development and Validation of a Sensitive, Fast and Simple LC-MS/MS Method for the Quantitation of Favipiravir Pure and Tablet Dosage Forms - Rao, Naidu Srinivasa; Adimulapu, Anil Kumar; Roja Kumari, M.; Rao, Pallepogu Venkateswara; Anusha, Abbineni; Thathapudi, Daveedu (Indian Journal of Pharmaceutical Education and Research, 2024)
Objectives The analytical method development and validation for the determination of Favipiravir (FVPR) in pure and tablet dosage forms by LC/MS-MS Technique. Materials and Methods A simple LC-MS/MS method was developed for the determination of a new antiviral drug, FVPR in pharmaceutical formulations the separation process was conducted using a Waters X-Bridge Phenyl Hexyl column (150x4.6 mm, 3.5 μm). The elution method employed was isocratic, involving a buffer solution consisting of 1 mL of Formic acid in 1 Litter of water. The mobile phase consisted of a mixture of two components: the aforementioned buffer and Acetonitrile in a 60:40 v/v ratio. The elution was maintained at a flow rate of 1 mL/min, as well as the entire process was carried out at room temperature. The proposed method was validated according to the International Conference on Harmonization (ICH) guidelines. The established method found better outcomes. Results The linearity graph was found in the range of 2-40 ngmL-1, and the correlation coefficient value (R2) obtained was found to be 0.9997. The limit of detection and limit of quantification were 4.044 ngmL-1 and 12.253 ngmL-1, respectively. Tremendous recovery outcomes were observed and found to be 99.49%, 100.09.0% and 100.21% for the FVPR at 150% upper, 100% middle and 50% lower concentrations, respectively. For studying Favipiravir, an electrospray ionization source was employed, with ion pairs of mass analysis at m/z 560.28→158.63 for Favipiravir and m/z 607.33→193.48 for the Internal Standard (IS), which was Zanamivir in this case. Conclusion All obtained outcomes were complying with the ICH guidelines. The developed method was simple, unique, accurate, robust, precise, and reproducible for the determination of FVPR in tablet formulation. The method is novel and could be adopted in the formulation industry.
Keywords: LC-MS/MS; Favipiravir; Zanamivir; Validation; Analytical method